PENGARUH KULIATAS PELAYANAN, PENGETAHUAN PERPAJAKAN DAN SANKSI PAJAK TERHADAP KEPATUHAN PAJAK DALAM PELAPORAN PAJAK TAHUNAN PADA PT JET TEKNOLOGI EXPRESS - Aulia Ayu Nur Fauziah; Imam Hidayat (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of service quality, taxpayer compliance and taxpayer sanctions on taxpayer compliance. In fact, tax evasion is becoming more common due to tax evasion violations. Therefore, the purpose of this study is to understand taxpayer compliance in the above aspects. This type of survey uses a quantitative survey. The data collection method used in this research is the questionnaire method. The data source uses primary data in the form of survey responses distributed to respondents. The analytical method used in drawing this conclusion is a multilinear analysis method with the help of SPSS version 21. The results of the analysis show that service quality has no significant effect on taxpayer compliance, and tax knowledge has a significant effect on taxpayer compliance..